Pertanggungjawaban Pidana Panitia Penerima Hasil Pekrjaan (PPHP) Pada Pengadaan Barang Dan Jasa Pemrintah - Sigid Budiyono (Fakultas Hukum Universitas Mataram, 2017)
This study intended to analyze about the shape of authority and criminal responsibility of the recepient procurement of goods and sevices government committee. Legal issues that arise in this study include: about the authority of the recipient procurement of goods and service government committee, and what defense criminal responsibility of the recipient procurement of goods and sevices government committee. This study is normative legal research based on the consideration that this study departs from the analysis of legislation that describes the scribes the scribes the scribes the authority and criminal responsibility of the recipient procurement of goods and sevices government committee. Approach to be adopted is the approach legislation approach to the concept and historial approach. Legal materials colletion techniques with study of literature. Based on the result of this study concluded this from authority recepient procurement of goods and sevices government committee. This authority Atribution that is the authority of the posititon, authority established together with the position tersebut, responsibility criminal of goods and services is a position responsibility in the recipient procurement on government and personal responsibility on procurement goods and services goverment